Canon, Narrative, and the Old Testament’s Literal Sense: A Response to John Goldingay - Seitz, Christopher R. (Tyndale bulletin, 2008)
A response to John Goldingay’s article, ‘Old Testament Theology and the Canon’ (TynBul 59.1: 1-26), calling attention to features which particularly struck the author as worthy of further reflection and critical evaluation.